2019
DOI: 10.2147/cia.s212980
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of oral environment on frailty: particular relevance of tongue pressure</p>

Abstract: PurposeOral frailty or the loss of oral functionality can be a symptomatic precursor of overall frailty. Previous studies have suggested that decreased tongue pressure causes a decline in ingesting and swallowing function and poor nutrition. This study investigated what factor(s) contribute to tongue pressure, thereby leading to frailty.Patients and methodsFor the purposes of the present study, 467 residents of Hirosaki city in northern Japan aged≥60 years who completed a questionnaire about frailty and underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 22 publications
(20 reference statements)
4
54
2
Order By: Relevance
“…The number of patients who exhibited a higher value than the threshold value in each oral function was also described. Although all oral functions were comparatively lower than those reported in previous studies [12,[22][23][24][25][26], the median value of masticatory function (114 mg/ dL, IQR: 73-167.5) was higher than a threshold value (100 mg/dL) and 27 of the 50 patients exceeded a threshold value. However, the patients in the present study demonstrated comparatively lower values of MOF (229.2 N, IQR: 110.2-419.6) and MTP (25.9 kPa, IQR: 21.4-29.0).…”
Section: Resultscontrasting
confidence: 73%
“…The number of patients who exhibited a higher value than the threshold value in each oral function was also described. Although all oral functions were comparatively lower than those reported in previous studies [12,[22][23][24][25][26], the median value of masticatory function (114 mg/ dL, IQR: 73-167.5) was higher than a threshold value (100 mg/dL) and 27 of the 50 patients exceeded a threshold value. However, the patients in the present study demonstrated comparatively lower values of MOF (229.2 N, IQR: 110.2-419.6) and MTP (25.9 kPa, IQR: 21.4-29.0).…”
Section: Resultscontrasting
confidence: 73%
“…In recent years, various cross-sectional and longitudinal studies have shown that frailty in community-dwelling older people is associated with decreases in oral functions such as occlusal force, tongue pressure and masticatory function. [9][10][11][12] Various items contribute to oral function; however, no standardized evaluation criteria for multiple oral functions have been determined. There is also little information on the effects of a combination of decreased oral functions on frailty.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, we did not perform any assessment of subject frailty in this study. Previous studies have suggested a relationship between tongue strength and frailty [3]. When the subject is an older adult, frailty affecting muscle strength should be assessed, such as with a cardiovascular health study index [45,46].…”
Section: %-85% N=3mentioning
confidence: 99%
“…The prevalence of frailty increases with age and the associated risk of health problems such as institutionalization, hospitalization, and falls, and death is recognized internationally [1,2]. Previous studies have linked tongue strength and frailty, and a decrease in tongue strength is known to affect feeding, swallowing functions, and nutrition [3]. In addition, the tongue plays an important role in swallowing, and weakening of the tongue muscles is one of the most common age-related changes in older individuals [4].…”
Section: Introductionmentioning
confidence: 99%